GXD's RNA-Seq and Microarray Experiment Search: using curated metadata to reliably find mouse expression studies of interest. (4th March 2020) - Smith, Constance M; Kadin, James A; Baldarelli, Richard M; Beal, Jonathan S; Blodgett, Olin; Giannatto, Sharon C; Richardson, Joel E; Ringwald, Martin
Abstract: The Gene Expression Database (GXD), an extensive community resource of curated expression information for the mouse, has developed an RNA-Seq and Microarray Experiment Search (http://www.informatics.jax.org/gxd/htexp_index ). This tool allows users to quickly and reliably find specific experiments in ArrayExpress and the Gene Expression Omnibus (GEO) that study endogenous gene expression in wild-type and mutant mice. Standardized metadata annotations, curated by GXD, allow users to specify the anatomical structure, developmental stage, mutated gene, strain and sex of samples of interest, as well as the study type and key parameters of the experiment. These searches, powered by controlled vocabularies and ontologies, can be combined with free text searching of experiment titles and descriptions. Search result summaries include link-outs to ArrayExpress and GEO, providing easy access to the expression data itself. Links to the PubMed entries for accompanying publications are also included. More information about this tool and GXD can be found at the GXD home page (http://www.informatics.jax.org/expression.shtml ). Database URL: http://www.informatics.jax.org/expression.shtml